博客
关于我
强烈建议你试试无所不能的chatGPT,快点击我
第20篇
阅读量:7185 次
发布时间:2019-06-29

本文共 13476 字,大约阅读时间需要 44 分钟。

\section{On a Class of Three-Variable Inequalities}%20

\markboth{Articles}{On a Class of Three-Variable Inequalities}

\vspace{4.2cm}

\subsection{Theorem}

Let $a,b,c$ be real numbers such that $a+b+c=1$.
By the AM-GM inequality,
$$ab+bc+ca\le \ds\f{1}{3},$$
therefore setting $ab+bc+ca=\ds\f{1-a^2}{3}$ $(q\ge 0)$,
we will find the maximum and minimum values of $abc$ in terms of $q$.
If $q=0$, then $a=b=c=\ds\f{1}{3}$,
therefore $abc=\ds\f{1}{27}$.
If $q\ne 0$, then
$(a-b)^2+(b-c)^2+(c-a)^2>0$.
Consider the function
$f(x)=(x-a)(x-b)(x-c)=x^3-x^2+\ds\f{1-q^2}{3}x-abc$.
We have
$$f'(x)=3x^2-2x+\ds\f{1-q^2}{3}$$
with zeros $x_1=\ds\f{1+q}{3}$ and $x_2=\ds\f{1-q}{3}$.
We can see that
$f'(x)<0$ for $x_2<x<x_1$ and $f'(x)>0$ for $x<x_2$ or $x>x_1$.
Furthermore, $f(x)$ has three zeros: $a,b,c$.
Then
$$f\left(\ds\f{1-q}{3}\right)=\ds\f{(1-q)^2(1+2q)}{27}-abc\ge 0$$
and
$$f\left(\ds\f{1+q}{3}\right)=\ds\f{(1+q)^2(1-2q)}{27}-abc\le 0.$$
Hence
$$\ds\f{(1+q)^2(1-2q)}{27}\le abc\le \ds\f{(1-q)^2(1+2q)}{27}$$
and we obtain the following theorem.

{\bf Theorem 1.}

{\it If $a,b,c,$ are arbitrary real numbers such that $a+b+c=1$,
and if $ab+bc+ca=\ds\f{1-q^2}{3}$ $(q\ge 0)$, then holds
$$\ds\f{(1+q)^2(1-2q)}{27}\le abc\le \ds\f{(1-q)^2(1+2q)}{27}.$$

}

Or, more generally,

{\bf Theorem 2.}

{\it Let $a,b,c$ be real numbers such that $a+b+c = p$.

If $ab+bc+ca =\ds\f{p^2-q^2}{3}$ $(q\ge 0)$ and $r=abc$, then

$$\ds\f{(p+q)^2(p-2q)}{27}\le r\le \ds\f{(p-q)^2(p+2q)}{27}.$$

This is a powerful tool because the equality holds if and only if

$$(a-b)(b-c)(c-a)=0.$$
Here are some identities which we can use with this theorem
$$a^2+b^2+c^2=\ds\f{p^2+2q^2}{3}$$
$$a^3+b^3+c^3=pq^2+3r$$
$$ab(a+b)+bc(b+c)+ca(c+a)=\ds\f{p(p^2-q^2)}{3}-3r$$
$$(a+b)(b+c)(c+a)=\ov{p(p^2-q^2)}{3}-r$$
$$a^2b^2+b^2c^2+c^2a^2=\ds\f{(p^2-q^2)^2}{9}-2pr$$
$$ab(a^2+b^2)+bc(b^2+c^2)+ca(c^2+a^2)
=\ds\f{(p^2+2q^2)(p^2-q^2)}{9}-pr$$
$$a^4+b^4+c^4=\ds\f{-p^4+8p^2q^2+2q^4}{9}+4pr.$$

}

 

{\bf Remark 1.}

There is also a geometric proof of this result.

By Viete's formulas we have

$$(x-a)(x-b)(x-c)=x^2-px^2+\ds\f{1}{3}(p^2-q^2)x-r.$$

As we increase $r$ we lower the graph of

$y=x^3-px^2+\ds\f{1}{3}(p^2-q^2)x-r$.
The largest and smallest values of $r$ for which this polynomial will have three real
roots will be at the points where it has double roots, with the maximum of $r$
corresponding to the case where the smaller root is the double root.
In this case we find the double root at $(p\mp q)/3$ and the single root at $(p\pm 2q)/3$
with the upper sign corresponding to the maximum of $r$ and the lower sign the minimum.

{\bf Remark 2.}
This result is sharp in the following sense.

Suppose we are given real numbers $p,q,r$ with $q\ge 0$ satisfying this inequality.

Then there exist real numbers $a,b,c$ such that $a + b + c = p$,
$ab+bc+ca=\ds\f{p^2-q^2}{3}$, and $abc=r$.

{\bf Remark 3.}

If $a,b,c\ge 0$ then we get the additional restrictions that $r\ge 0$
and $p\ge q$.

This remark is used in the last application so it might be worth making

even if you ignore the others.
Alternately, one can state it with all three
inequalities strict.
For a monic cubic polynomial $p(x)=(x-a)(x-b)(x-c)$
the discriminant of the polynomial $p$ is
$D=(a-b)^2(b-c)^2(c-a)^2$.
This is a symmetric polynomial in the roots of $p$, therefore it can be written as a
polynomial in the coefficients of $p$.
In the special case above where
$p(x)=x^3-px^2+\ds\f{1}{3}(p^2-q^2)x-r$
one can compute that
$$D=27\left(r-\ds\f{(p+q)^2(p-2q)}{3}\right)\left(\ds\f{(p-q)^2(p+2q)}{3}-r\right).$$

With this formula Theorem 2 and its converse combine to give the well known

fact that the discriminant is nonnegative if and only if p has only real roots.

\subsection{Applications}

{\bf Problem 1.}
{\it Let $a,b,c$ be positive real numbers such that $a+b+c = 1$.
Prove that
$$\ds\f{1}{a}+\ds\f{1}{b}+\ds\f{1}{c}+48(ab+bc+ca)\ge 25.$$

}

{\bf Solution.}

We can easily check that $q\in [0,1]$, and by using Theorem 2,
\begin{align*}
{\rm LHS}
& =\ds\f{1-q^2}{3r}+16(1-q^2)\ge \ds\f{9(1+q)}{(1-q)(1+2q)}+16(1-q^2)\\
& =\ds\f{2q^2(4q-1)^2}{(1-q)(1+2q)}+25\ge 25.
\end{align*}

The inequality is proved.

Equality holds if and only if $a = b = c = \ds\f{1}{3}$
or $a=\ds\f{1}{2}$, $b=c=\ds\f{1}{4}$
and their permutations.

{\bf Problem 2.}

(Vietnam 2002).
{\it Let $a,b,c$ be real numbers such that $a^2+b^2+c^2=9$.
Prove that
$$2(a+b+c)-abc\le 10.$$

}

{\bf Solution.}

The condition can be written as
$p^2+2q^2=27$.
Using our theorem, we have
$${\rm LHS}=2p-r\le 2p-\ds\f{(p+q)^2(p-2q)}{27}=\ds\f{p(5q^2+27)+2q^3}{27}.$$

We need to prove that

$$p(5q^2+27)\le 270-2q^3.$$

This follows from

$$(270-2q^3)^2\ge p^2(5q^2+27)^2,$$
or, equivalently,
$$27(q-3)^2(2q^4+12q^3+49q^2+146q+219)\ge 0.$$

The inequality is proved.

Equality holds if and only if $a = b = 2$, $c = -1$ and
their permutations.

{\bf Problem 3.}

(Vo Quoc Ba Can).
{\it For all positive real numbers $a,b,c$,
$$\ds\f{a+b}{c}+\ds\f{b+c}{a}+\ds\f{c+a}{b}+11\sqrt {\ds\f{ab+bc+ca}{a^2+b^2+c^2}}\ge 17.$$

}

{\bf Solution.}

Because the inequality is homogeneous, without loss of generality,
assume that $p = 1$.
Then $q\in [0,1]$ and the inequality can be written as
$$\ds\f{1-q^2}{3r}+11\sqrt {\ds\f{1-q^2}{1+2q^2}}\ge 20.$$

By our theorem, it suffices to prove

$$11\sqrt {\ds\f{1-q^2}{1+2q^2}}\ge 20-\ds\f{9(1+q)}{(1-q)(1+2q)}
=\ds\f{-40q^2+11q+11}{(1-q)(1+2q)}.$$

If $-40q^2+11q+11\le 0$,

or
$q\ge \ds\f{11+3\sqrt {209}}{80}$,
it is trivial.
If
$q\le \ds\f{11+3\sqrt {209}}{80}<\ds\f{2}{3}$,
$$\ds\f{121(1-q^2)}{1+2q^2}-\ds\f{(-40q^2+11q+11)^2}{(1-q)^2(1+2q)^2}
=\ds\f{3q^2(11-110q+255q^2+748q^3-1228q^4)}{(1+2q^2)(1-q)^2(1+2q)^2}.$$

Note that the only positive real root of

$11-110q+255q^2+748q^3-1228q^4$
is at $0.748037\ldots >\ds\f{11+3\sqrt {209}}{80}$
and therefore the numerator is positive for $q\le \ds\f{11+3\sqrt {209}}{80}$.
The inequality is proved.
Equality occurs if and only if $a = b = c$.

{\bf Problem 4.}

(Vietnam TST 1996).
{\it Prove that for any $a,b,c\in \mathbb{R}$,
$$(a+b)^4+(b+c)^4+(c+a)^4\ge \ds\f{4}{7}(a^4+b^4+c^4).$$

}

{\bf Solution.}

If $p = 0$ the inequality is trivial, so we will consider the case $p\ne 0$.
Without loss of generality, assume that $p = 1$.
The inequality becomes
$$q^4+4q^2+10-108r\ge 0$$
and by our theorem
\begin{align*}
q^4+4q^2+10-108r
& \ge q^4+4q^2+10-4(1-q)^2(1+2q)\\
& =q^2(q-4)^2+6\ge 0.
\end{align*}

The inequality is proved.
Equality holds only for $a = b = c = 0$.

{\bf Problem 5.}

(Pham Huu Duc, MR1/2007).
{\it Prove that for any positive real numbers $a,b,c$,
$$\sqrt {\ds\f{b+c}{a}}+\sqrt {\ds\f{c+a}{b}}+\sqrt {\ds\f{a+b}{c}}
\ge \sqrt {6\cdot \ds\f{a+b+c}{\sqrt [3]{abc}}}.$$

}

{\bf Solution.}

By H\"older's inequality,
$$\left(\sum_{cyc}\sqrt {\ds\f{b+c}{a}}\right)^2
\left(\sum_{cyc}\ds\f{1}{a^2(b+c)}\right)\ge \left(\sum_{cyc}\ds\f{1}{a}\right)^3.$$

It suffices to prove that
$$\left(\sum_{cyc}\ds\f{1}{a}\right)^3\ge \ds\f{6(a+b+c)}{\sqrt [3]{abc}}
\sum_{cyc}\ds\f{1}{a^2(b+c)}.$$

Let $x=\ds\f{1}{a}$, $y=\ds\f{1}{b}$, $z=\ds\f{1}{c}$,

then the inequality becomes
$$(x+y+z)^3\ge 6\sqrt [3]{xyz}(xy+yz+zx)\sum_{cyc}\ds\f{x}{y+z},$$
or
$$(x+y+z)^3\ge \ds\f{6\sqrt [3]{xyz}(xy+yz+zx)}{(x+y)(y+z)(z+x)}
((x+y+z)^3-2(x+y+z)(xy+yz+zx)+3xyz).$$

By the AM-GM inequality,

$$(x+y)(y+z)(z+x)=(x+y+z)(xy+yz+zx)-xyz
\ge \ds\f{8}{9}(x+y+z)(xy+yz+zx).$$

It remains to prove that

$$4(x+y+z)^4\ge 27\sqrt [3]{xyz}((x+y+z)^3-2(x+y+z)(xy+yz+zx)+3xyz).$$

Setting $p=x+y+z$, $xy+yz+zx=\ds\f{p^2-q^2}{3}$ $(p\ge q\ge 0)$,

the inequality becomes
$$4p^4\ge 9\sqrt [3]{xyz}(p^3+2pq^2+9xyz).$$

Applying our theorem, it suffices to prove that

$$4p^4\ge 9\sqrt [3]{\ds\f{(p-q)^2(p+2q)}{27}}
\left(p^3+2pq^2+\ds\f{(p-q)^2(p+2q)}{3}\right)$$
$$4p^4\ge \sqrt [3]{(p-q)^2(p+2q)}(3p^3+6pq^2+(p-q)^2(p+2q)).$$

Setting $u=\sqrt [3]{\ds\f{p-q}{p+2q}}\le 1$,

the inequality is equivalent to
$$4(2u^3+1)^4\ge 27u^2(4u^9+5u^6+2u^3+1),$$
or
$$f(u)=\ds\f{(2u^3+1)^4}{u^2(4u^9+5u^6+2u^3+1)}\ge \ds\f{27}{4}.$$

We have

$$f'(u)=\ds\f{2(2u^3+1)^3(u^3-1)(2u^3-1)(2u^6+2u^3-1)}{u^3(u^3+1)^2(4u^6+u^3+1)^2}$$
and
$$f'(u)=0\Lr u=\sqrt [3]{\ds\f{\sqrt 3-1}{2}},\ds\f{1}{\sqrt [3]{2}},1.$$
Now, we can easily verify that
$$f(u)\ge \min\left\{f\left(\sqrt [3]{\ds\f{\sqrt 3-1}{2}}\right),f(1)\right\}=\ds\f{27}{4},$$
which is true.
The inequality is proved.
Equality holds if and only if $a = b = c$.

{\bf Problem 6.}

(Darij Grinberg).
{\it If $a,b,c\ge 0$, then
$$a^2+b^2+c^2+2abc+1\ge 2(ab+bc+ca).$$

}

{\bf Solution.}

Write the inequality as
$$6r+3+4q^2-p^2\ge 0.$$
If $2q\ge p$, it is trivial.
If $p\ge 2q$, using the theorem, it suffices to prove that
$$\ds\f{2(p-2q)(p+q)^2}{9}+3+4q^2-p^2\ge 0,$$
or
$$(p-3)^2(2p+3)\ge 2q^2(2q+3p-18).$$

If $2p\le 9$, we have $2q+3p\le 4p\le 18$,

therefore the inequality is true.
If $2p\ge 9$, we have
$$2q^2(2q+3p-18)\le 4q^2(2p-9)\le p^2(2p-9)$$
$$=(p-3)^2(2p+3)-27<(p-3)^2(2p+3).$$

The inequality is proved.

Equality holds if and only if $a = b = c = 1$.

{\bf Problem 7.}
(Schur's inequality).
{\it For all nonnegative real numbers $a,b,c$,
$$a^3+b^3+c^3+3abc\ge ab(a+b)+bc(b+c)+ca(c+a).$$

}

{\bf Solution.}

Because the inequality is homogeneous, we can assume that
$a+b+c=1$.
Then $q\in [0,1]$ and the inequality is equivalent to
$$27r+4q^2-1\ge 0.$$

If $q\ge \ds\f{1}{2}$, it is trivial.

If $q\le \ds\f{1}{2}$,
by the theorem we need to prove that
$$(1+q)^2(1-2q)+4q^2-1\ge 0,$$
or
$$q^2(1-2q)\ge 0,$$
which is true.
Equality holds if and only if $a = b = c$ or $a = b$, $c = 0$ and their permutations.

{\bf Problem 8.}

(Pham Huu Duc).
{\it For all positive real numbers $a,b,c$,
$$\ds\f{1}{a^2+bc}+\ds\f{1}{b^2+ca}+\ds\f{1}{c^2+ab}
\le \ds\f{(a+b+c)^2}{3(ab+bc+ca)}
\left(\ds\f{1}{a^2+b^2}+\ds\f{1}{b^2+c^2}+\ds\f{1}{c^2+a^2}\right).$$

}

{\bf Solution.}

Because the inequality is homogeneous, we may assume that $p=1$.
Then $q\in [0,1]$,
and by the AM-GM and Schur's inequalities, we have
$$\ds\f{(1-q^2)^2}{9}\ge 3r\ge \max\left\{0,\ds\f{1-4q^2}{9}\right\}.$$
After expanding, we can rewrite the given inequality as
$$f(r)=-486(9-q^2)r^3+27(q^6+64q^4-35q^2+24)r^2$$
$$+9(4q^2-1)(11q^4-4q^2+2)r+q^2(1-q^2)^3(2q^4+8q^2-1)\ge 0.$$

We have

$$f'(r)=9-162(9-q^2)r^2+6(q^6+64q^4-35q^2+24)r
+(4q^2-1)(11q^4-4q^2+2)$$
$$f''(r)=54(-54(9-q^2)r+q^6+64q^4-35q^2+24)$$
$$\ge 54(-2(1-q^2)^2(9-q^2)+q^6+64q^4-35q^2+24)
=162(q^6+14q^4+q^2+2)>0.$$

Hence $f'(r)$ is an increasing function.

Now, if $1\le 2q$, then
$$f'(r)\ge f'(0)=9(4q^2-1)(11q^4-4q^2+2)\ge 0.$$

If $1\ge 2q$, then

$$f'(r)\ge f'\left(\ds\f{1-4q^2}{27}\right)=(1-4q^2)(q^2+2)(2q^4+17q^2+6)\ge 0.$$

In each case, $f(r)$ is an increasing function.

If $1\le 2q$, then
$$f(r)\ge f(0)=q^2(1-q^2)^3(2q^4+8q^2-1)\ge 0,$$
and we are done.
If $1\ge 2q$, by our theorem,
$$f(r)\ge f\left(\ds\f{(1+q)^2(1-2q)}{27}\right)$$
$$=\ds\f{1}{81}q^2(2-q)(q+1)^2(6q^3+4q^2-7q+4)(5q^2-2q+2)^2\ge 0.$$

The proof is complete.

Equality holds if and only if $a = b = c$.

{\bf Problem 9.}

(Nguyen Anh Tuan).
{\it Let $x,y,z$ be positive real numbers such that
$xy + yz + zx + xyz = 4$.
Prove that
$$\ds\f{x+y+z}{xy+yz+zx}\le 1+\ds\f{1}{48}((x-y)^2+(y-z)^2+(z-x)^2).$$

}

{\bf Solution.}

Since $x,y,z>0$ and $xy+yz+zx+xyz=4$, there are $a,b,c>0$ such that
$x=\ds\f{2a}{b+c}$, $y=\ds\f{2b}{c+a}$, $z=\ds\f{2c}{a+b}$.
The inequality becomes
$$P(a,b,c)=\ds\f{(a+b+c)^2\ds\sum_{cyc}(a^2-b^2)^2}{(a+b)^2(b+c)^2(c+a)^2}
-\ds\f{6\ds\sum_{cyc}a(a+b)(a+c)}{\ds\sum_{cyc}ab(a+b)}+12\ge 0.$$

Because the inequality is homogeneous we can assume that $p = 1$.
Then
$q\in [0,1]$,
and after some computations, we can write the inequality as
$$f(r)=729r^3+27(22q^2-1)r^2+27(6q^4-4q^2+1)r+(q^2-1)(13q^4-5q^2+1)\le 0.$$

We have

$$f'(r)=27(r(81r+44q^2-2)+6q^4-4q^2+1).$$

By Schur's inequality,

$$81r+44q^2-2\ge 3(1-4q^2)+44q^2-2=1+32q^2>0.$$

Hence $f'(r)\ge 0$, and $f(r)$ is an increasing function.

Then by our theorem,
$$f(r)\!\le\! f\left(\ds\f{(1-q)^2(1+2q)}{27}\right)
=\ds\f{2}{27}q^2(q-1)(q+2)^2(4q^4+14q^3+15q^2-7q+1)\!\le 0.$$

The inequality is proved.

Equality holds if and only if $x = y = z$.

{\bf Problem 10.}

(Nguyen Anh Tuan).
{\it For all nonnegative real numbers $a,b,c$,
$$\sqrt {(a^2-ab+b^2)(b^2-bc+c^2)}
+\sqrt {(b^2-bc+c^2)(c^2-ca+a^2)}$$
$$+\sqrt {(c^2-ca+a^2)(a^2-ab+b^2)}
\ge a^2+b^2+c^2.$$

}

{\bf Solution.}

After squaring both sides, we can rewrite the inequality as
$$2\sqrt {\ds\prod_{cyc}(a^2-ab+b^2)}\left(\sum_{cyc}\sqrt {a^2-ab+b^2}\right)
\ge \left(\sum_{cyc}ab\right)\left(\sum_{cyc}a^2\right)-\sum_{cyc}a^2b^2.$$

By the AM-GM inequality,

$$\sqrt {a^2-ab+b^2}\ge \ds\f{1}{2}(a+b),\
\sqrt {b^2-bc+c^2}\ge \ds\f{1}{2}(b+c),\
\sqrt {c^2-ca+a^2}\ge \ds\f{1}{2}(c+a).$$

It suffices to prove that

$$2\sqrt {\ds\prod_{cyc}(a^2-ab+b^2)}\left(\sum_{cyc}a\right)
\ge \left(\sum_{cyc}ab\right)\left(\sum_{cyc}a^2\right)-\sum_{cyc}a^2b^2.$$

Because this inequality is homogeneous, we can assume $p = 1$.
Then $q\in [0,1]$
and the inequality is equivalent to
$$2\sqrt {-72r^2+3(1-10q^2)r+q^2(1-q^2)^2}\ge 6r+q^2(1-q^2),$$
or
$$f(r)=324r^2-12r(q^4-11q^2+1)-q^2(4-q^2)(1-q^2)^2\le 0.$$

It is not difficult to verify that $f(r)$ is a convex function, then by our theorem,

$$f(r)\le \max\left\{f(0),f\left(\ds\f{(1-q)^2(1+2q)}{27}\right)\right\}.$$

Furthermore,

$$f(0)=-q^2(4-q^2)(1-q^2)^2\le 0$$
$$f\left(\ds\f{(1-q)^2(1+2q)}{27}\right)
=\ds\f{1}{9}q^2(q-1)^3(q+2)(9q^2+q+2)\le 0.$$

Our proof is complete.

Equality holds if and only if $a = b = c$ or $a=t\ge 0$,
$b = c = 0$, and their permutations.

\bigskip

\hfill
{\Large Vo Quoc Ba Can, Vietnam}

%%%%%%%

转载于:https://www.cnblogs.com/Eufisky/p/7802100.html

你可能感兴趣的文章
SQL夯实基础(八):联接运算符算法归类
查看>>
如何使用JMeter来实现更大批量的并发的解决方案(即如何设置controller和Agent)
查看>>
第七天
查看>>
Linux 必会
查看>>
HTML骨架结构
查看>>
【哈希表】CodeVs1230元素查找
查看>>
自定义上传图片样式并实现上传立即展示该图片
查看>>
通达OA 自定义菜单
查看>>
Excutors 线程池
查看>>
BootStrap的table技术小结:数据填充、分页、列宽可拖动
查看>>
用HTML做的简单的个人简历
查看>>
MySQL高级 之 order by、group by 优化
查看>>
POJ3320:Jessica's Reading Problem(尺取法)
查看>>
Mysql学习——安装登录
查看>>
React-nwb的使用
查看>>
【人生思考】2015读书清单
查看>>
Vim的多窗口模式管理
查看>>
我的Android进阶之旅------>Android实现用Android手机控制PC端的关机和重启的功能(三)Android客户端功能实现...
查看>>
mysql在CentOS6.3上安装
查看>>
Leetcode 665. Non-decreasing Array(Easy)
查看>>